Characterization of the intracelular signalling pathways mediating the effects of purinergic receptors in dendritic and axonal formation and outgrowth - Rocha, João Miguel Miranda da (2019)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia